Microcapsule composite carbonyl iron powder coated with organic material and preparation method thereof

By covering the surface of the carbonyl iron powder with modifiers and preservatives, and then covering a layer of resin to form a double shell structure, the problem of corrosion of the carbonyl iron powder in a high humidity and high salt spray environment is solved, and the double improvement of its electromagnetic properties and corrosion resistance is achieved.

CN115458314BActive Publication Date: 2025-03-14UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210853647.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-03-14
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

Carbonyl iron powder is prone to corrosion in high humidity and high salt spray environments, resulting in unstable electromagnetic properties. Existing modification methods often damage their electromagnetic properties.

Method used

The preparation method of microcapsule composite carbonyl iron powder coated with organic materials is formed by coating the surface of the carbonyl iron powder with a modifier and preservative, and then coating a layer of resin to form a bi-shell structure of resin, preservative, carbonyl iron powder.

Benefits of technology

On the premise of ensuring that the electromagnetic properties of carbonyl iron powder do not deteriorate, its corrosion resistance is significantly improved and can remain stable in a salt spray environment for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115458314B_ABST
    Figure CN115458314B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electromagnetic microwave absorbers, and relates to corrosion protection of carbonyl iron powder, specifically a microcapsule composite carbonyl iron powder coated with an organic material and a preparation method thereof. The present invention adopts an in-situ polymerization method, firstly coats a layer of modifier and preservative on the carbonyl iron powder, and then coats a layer of resin through a cross-linking curing reaction, and finally forms a double-shell structure of resin @ preservative @ carbonyl iron powder. The materials used in the present invention are all organic materials, and are all low-dielectric materials, which can reduce the dielectric properties of carbonyl iron powder, optimize impedance matching, and improve reflection loss. Finally, the present invention significantly improves the acid resistance, electrochemical corrosion resistance, and salt spray resistance of the modified powder without much deterioration of the electromagnetic properties of the powder, and can achieve coating for carbonyl iron powders of various shapes, providing a new solution for improving the corrosion resistance of carbonyl iron powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic microwave absorbers, and relates to corrosion protection of carbonyl iron powder. Carbonyl iron powder can be used as a microwave absorber in high humidity and high salt fog environments, and specifically relates to a microcapsule composite carbonyl iron powder coated with an organic material and a preparation method thereof, which has both good corrosion resistance and excellent microwave absorption performance. Background Art

[0002] Carbonyl iron powder is a traditional magnetic absorbent with advantages such as high magnetic permeability and high saturation magnetization intensity, and is widely used in the field of microwave absorption. Because of its large specific surface area, the number of atoms on the surface of the material is relatively increased, so the area of ​​interaction with electromagnetic waves is increased, which is conducive to the conversion of electromagnetic waves into heat energy or other forms of energy and loss. Carbonyl iron powder is obtained by thermal decomposition of carbonyl iron compounds in a preheated nitrogen atmosphere. It has a unique onion ball layered structure and has a high resistivity, which is conducive to suppressing eddy current effects and reducing the adverse effects caused by skin effects. Therefore, carbonyl iron powder is a common microwave absorbent material for thin-layer absorbing coatings and is widely used in important fields such as military.

[0003] In recent years, in the application field of microwave absorbers in marine environments, carbonyl iron powder is easily oxidized to produce iron oxide and other substances due to its small particle size and high surface activity, which loses its physical structure and characteristics, making it unfavorable for the application of carbonyl iron powder. Therefore, the research on the corrosion resistance of carbonyl iron powder has received extensive attention, and it is necessary to achieve the long-term stability of the electromagnetic properties of carbonyl iron powder in a salt spray and humid environment.

[0004] In current research, most researchers have modified the surface of carbonyl iron powder inorganically or organically to form a continuous, uniform and dense inorganic or organic protective layer on the surface of carbonyl iron powder. Inorganic materials, such as coating the surface of carbonyl iron powder with Ag layer, Co layer, Ni layer, and the common research is to coat a layer of SiO2 material, etc.; organic materials, such as coating the surface of carbonyl iron powder with a layer of polyaniline, cholesterol chloroformate and other organic materials. These inorganic and organic materials can provide protection for carbonyl iron powder in salt spray and humid environment, isolating oxygen and other corrosive media.

[0005] Patent CN113388231A first modifies the surface of carbonyl iron powder with a silane coupling agent, then mixes the treated carbonyl iron powder with epoxy resin, stirs, and solidifies, and finally obtains epoxy resin-coated carbonyl iron powder absorbing material. This method first treats the carbonyl iron powder with a silane coupling agent, which deteriorates the electromagnetic properties of the carbonyl iron powder to a certain extent. At the same time, the surface of the powder obtained by the preparation method after epoxy resin coating is rough and uneven, and it is impossible to completely isolate corrosive media such as water vapor, oxygen, chloride ions, etc. The modified carbonyl iron powder has general corrosion resistance.

[0006] Patent CN112563010A uses a "hydrolysis-pyrolysis" method to coat the iron powder with a dense thick coating of silicon dioxide, making it have good salt water / salt spray corrosion resistance. This method uses silicon dioxide to coat the powder, which has the problem of serious deterioration of electromagnetic properties.

[0007] Patent CN110722153B provides an antioxidant absorbent and a preparation method thereof, wherein aluminum powder is evenly attached to the surface of spherical carbonyl iron powder, and oxidation is controlled to form a dense Al2O3-coated carbonyl iron powder antioxidant absorbent. The powder coating layer is dense and continuous, and the corrosion resistance is improved. However, there is also the problem of serious deterioration of the electromagnetic properties of the modified powder. Summary of the invention

[0008] In view of the problems or deficiencies in the above research, in order to solve the problem of the current carbonyl iron powder in having both excellent electromagnetic properties and corrosion resistance, the present invention provides a microcapsule composite carbonyl iron powder coated with an organic material and a preparation method thereof, which ensures that the electromagnetic properties of the carbonyl iron powder are not deteriorated while taking into account excellent corrosion resistance.

[0009] A method for preparing microcapsule composite carbonyl iron powder coated with organic material comprises the following steps:

[0010] Step 1: Dissolve the preservative and modifier in an organic solvent at room temperature to obtain a mixture A. In the mixture A, the preservative accounts for 12% to 24%, the modifier accounts for 12% to 24%, and the organic solvent accounts for 52% to 76% by mass, and the sum of the three is 1.

[0011] The preservative is one or more of 2-amino-4-methylpyridine, N,N'-di(diphenylphosphino)-1-phenylethylamine, and n-hexadecylamine;

[0012] The modifier is one or two of diethylaminopropylamine, triethylenetetramine and hexamethylenediamine;

[0013] Step 2: Add carbonyl iron powder to the mixture A obtained in step 1 and disperse evenly to obtain a mixture B. In the mixture B, the carbonyl iron powder accounts for 30% to 50% by mass, the mixture A accounts for 50% to 70% by mass, and the sum of the two accounts for 1.

[0014] Step 3: Filter the mixture B obtained in step 2, wash it with deionized water, and then dry it in vacuum to obtain carbonyl iron powder coated with a layer of modifier and preservative.

[0015] Step 4: dissolving the resin in an organic solvent to obtain a mixture C. In the mixture C, the resin accounts for 2% to 8% by mass, the organic solvent accounts for 92% to 98% by mass, and the sum of the two accounts for 1.

[0016] Step 5: Add a crosslinking aid, an emulsifier and the carbonyl iron powder obtained in step 3 to the mixture C obtained in step 4, and then heat and stir the mixture until the crosslinking reaction is complete to obtain a mixture D.

[0017] In mixture D, by mass fraction, the crosslinking agent accounts for 1% to 4%, the emulsifier accounts for 1% to 4%, the carbonyl iron powder accounts for 7% to 14%, and the mixture C accounts for 78% to 91%, and the sum of the four is 1.

[0018] The cross-linking auxiliary agent is one or two of phthalic anhydride, tetrahydrophthalic anhydride and N,N-dimethylpiperazine; the emulsifier is one or two of sorbitan monooleate, sorbitan monooleate and sodium dodecyl sulfate.

[0019] Step 6: Cool the mixture D obtained in step 5 to room temperature, and then perform suction filtration, deionized water washing and vacuum drying in sequence to finally obtain microcapsule composite carbonyl iron powder coated with organic material.

[0020] Furthermore, the organic solvent is acetone, xylene, n-butanol or ethanol.

[0021] Furthermore, the carbonyl iron powder is spherical, so that the finally obtained microcapsule composite carbonyl iron powder coated with organic material has better corrosion resistance.

[0022] Furthermore, the carbonyl iron powder is in the form of flakes, so that the finally obtained microcapsule composite carbonyl iron powder coated with organic material has better electromagnetic properties.

[0023] A microcapsule composite carbonyl iron powder coated with an organic material is prepared by the method.

[0024] The present invention adopts an in-situ polymerization method, in which the reaction monomers, with the assistance of a catalyst, undergo copolymerization on the surface of the coated core material to generate a prepolymer, and as the reaction proceeds, the prepolymer continuously reacts to form a high molecular weight copolymer covering the surface of the core material. The adsorption of the modifier and preservative on the surface of the carbonyl iron powder in the present invention belongs to chemical adsorption. Researchers generally believe that transition metal atoms such as iron and nickel have empty d orbitals and are easy to accept electrons. In most organic molecules, polar groups with nitrogen, oxygen, sulfur, and phosphorus as central atoms have a certain electron-donating ability, and the two can form coordination bonds to cause chemical adsorption. The chemical adsorption has a large force, high adsorption heat, and the required activation energy is greater than that of physical adsorption, which is about 41.8×102kJ / mol. Chemical adsorption proceeds slowly, and once adsorbed, it is difficult to desorb, and the adsorption is irreversible. The purpose of step 1 is to coat the carbonyl iron powder with a layer of modifier and preservative. The role of the modifier is to be adsorbed on the surface of the carbonyl iron powder and react chemically with the epoxy resin in step 5 to improve the adhesion between the epoxy resin and the powder surface; the role of the preservative is to be adsorbed on the surface of the carbonyl iron powder and can effectively prevent the corrosion of the carbonyl iron powder. In step 5, the epoxy resin is cross-linked with the cross-linking aid on the carbonyl iron powder coated with a layer of modifier and preservative, and finally a double-shell structure of resin @ preservative @ carbonyl iron powder is formed. This double-shell structure will separate corrosive media such as water vapor, oxygen, and chloride ions in a long-term salt spray environment. If the resin ages and falls off during long-term use, the preservative adsorbed on the surface of the carbonyl iron powder will be exposed to the salt spray environment and continue to protect the carbonyl iron powder from corrosion. In addition, the materials used are all organic materials and low-dielectric materials, which can reduce the dielectric properties of the carbonyl iron powder, optimize impedance matching, and improve reflection loss.

[0025] In summary, the preparation process of the present invention is mature and simple, the raw material price is low, and it is suitable for mass production. By first preparing a layer of modifier and preservative on the surface of carbonyl iron powder, and then coating a layer of resin, the electromagnetic properties of the microcapsule composite carbonyl iron powder finally prepared are less deteriorated, and the salt spray corrosion resistance is excellent; and carbonyl iron powders of various shapes can be coated. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are SEM images of the uncoated sample and Examples 1 to 3.

[0027] Figure 2 The polarization curves of the uncoated powder and the powder of Examples 1 to 3 tested in 3.5% NaCl solution.

[0028] Figure 3 These are the acid resistance test results of the uncoated powder and the powders of Examples 1 to 3.

[0029] Figure 4 It is a simplified flow chart of the preparation of the present invention. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described in detail below in conjunction with implementation cases and drawings, but this does not limit the applicable scope of the present invention.

[0031] Example 1

[0032] Step 1: Dissolve 4 g of 2-amino-4-methylpyridine and 8 g of triethylenetetramine in 200 ml of xylene at room temperature of 25° C. to obtain a mixture A.

[0033] Step 2: Disperse 8 g of spherical carbonyl iron powder E in the mixture A obtained in step 1, stir at room temperature of 25° C. for 24 hours at a rotation speed of 400 RPM to obtain a mixture B.

[0034] Step 3: Filter the mixture B obtained in step 2, wash it with deionized water for several times, and dry it in vacuum to obtain a spherical carbonyl iron powder E coated with a layer of 2-amino-4-methylpyridine and triethylenetetramine.

[0035] Step 4: Dissolve 2.4 g of epoxy resin in 100 ml of xylene to obtain a mixture C.

[0036] Step 5. Add 0.5 g of phthalic anhydride, 0.1 g of sorbitan monooleate and the spherical carbonyl iron powder E obtained in step 3 to the mixture C obtained in step 4, and then carry out the cross-linking reaction at 80° C. and 550 RPM stirring for 8 hours until the reaction is complete to obtain a mixture D.

[0037] Step 6: After the mixture D obtained in step 5 is cooled to room temperature, it is subjected to magnetic separation, deionized water washing and vacuum drying in sequence to finally obtain microcapsule composite flaky carbonyl iron powder E coated with organic material.

[0038] Example 2

[0039] Step 1: Under room temperature of 25° C., 8 g of N,N′-di(diphenylphosphino)-1-phenylethylamine and 16 g of triethylenetetramine were dissolved in 400 ml of xylene to obtain a mixture A.

[0040] Step 2: Disperse 16 g of flaky carbonyl iron powder F in the mixture A obtained in step 1, stir at room temperature of 25° C. for 24 hours at a rotation speed of 500 RPM to obtain a mixture B.

[0041] Step 3: Filter the mixture B obtained in step 2, wash it with deionized water for several times, and dry it in vacuum to obtain a flaky carbonyl iron powder F coated with a layer of N,N'-di(diphenylphosphino)-1-phenylethylamine and triethylenetetramine.

[0042] Step 4: Dissolve 4.8 g of epoxy resin in 200 ml of xylene to obtain a mixture C.

[0043] Step 5. Add 0.6 g of N,N-dimethylpiperazine, 0.3 g of sodium dodecyl sulfate and the flaky carbonyl iron powder F obtained in step 3 to the mixture C obtained in step 4, and then carry out the cross-linking reaction at 75° C. and 650 RPM stirring for 8 hours until completion to obtain a mixture D.

[0044] Step 6: After the mixture D obtained in step 5 is cooled to room temperature, it is subjected to magnetic separation, deionized water washing and vacuum drying in sequence to finally obtain microcapsule composite flaky carbonyl iron powder F coated with organic material.

[0045] Example 3

[0046] Step 1: Under room temperature of 25° C., 8.5 g of n-hexadecylamine and 14 g of diethylaminopropylamine were dissolved in 400 ml of xylene to obtain a mixture A.

[0047] Step 2: Disperse 16 g of spherical carbonyl iron powder G in the mixture A of step 1, stir at room temperature of 25° C. for 24 hours at a rotation speed of 500 RPM to obtain a mixture B.

[0048] Step 3: Filter the mixture B obtained in step 2, wash it with deionized water for several times, and dry it in vacuum to obtain a spherical carbonyl iron powder G coated with a layer of n-hexadecylamine and diethylaminopropylamine.

[0049] Step 4: Dissolve 4.8 g of epoxy resin in 200 ml of xylene to obtain a mixture C.

[0050] Step 5. Add 0.4 g of tetrahydrophthalic anhydride, 0.3 g of sodium dodecyl sulfate and the spherical carbonyl iron powder G obtained in step 3 to the mixture C obtained in step 4, and then carry out the cross-linking reaction at 90° C. and 550 RPM stirring for 8 hours until completion to obtain a mixture D.

[0051] Step 6: After the mixture D obtained in step 5 is cooled to room temperature, it is subjected to magnetic separation, deionized water washing and vacuum drying in sequence to finally obtain microcapsule composite flaky carbonyl iron powder G coated with organic material.

[0052] For the sample results of the above three groups of implementation cases, three methods were used to characterize the corrosion resistance of the corrosion-resistant magnetic metal powder: ① Use an electrochemical workstation to test the electrochemical corrosion resistance of the corrosion-resistant magnetic metal powder in a 3.5% NaCl solution; ② Place the corrosion-resistant magnetic metal powder in a hydrochloric acid solution with a pH of 1, and stir the hydrochloric acid solution at the same time to measure the change in the pH of the solution. ③ Add the corrosion-resistant magnetic metal powder to the resin coating formula to prepare a coating, conduct a salt spray test, and regularly observe the changes on the coating surface.

[0053] Table 1 is a table of electromagnetic parameters measured by a vector grid analyzer in the range of 1-18 GHz for coaxial samples of powders before and after coating in Examples 1, 2, and 3. The comparison of the changes in electromagnetic parameters before and after coating shows that coating has little effect on the electromagnetic properties of powders, and the process is feasible.

[0054] Table 1: Comparison of electromagnetic parameters of samples prepared from powders before and after coating in each example.

[0055]

[0056]

[0057]

[0058] Table 2 is a comparison table of the salt spray resistance of the coatings prepared from the powders before and after coating in Examples 1, 2, and 3. The test results show that the corrosion resistance of the coated powders is significantly improved, and the powders have excellent corrosion resistance.

[0059] Table 2: Comparison of salt spray resistance time of coatings prepared from powders before and after coating in each example.

[0060]

[0061] Figure 4 It is a simple schematic diagram of the preparation method of the present invention. Figure 1 The SEM images of the powders before and after coating in Examples 1, 2 and 3 show that a tight and continuous organic layer is obviously present on the surface of the coated powders, which can provide long-term protection for the powders. This process is applicable to both spherical powders and flake powders. Figure 2 These are the polarization curves of the powders of Examples 1, 2 and 3 before and after coating in a 3.5% NaCl solution. After the three powders are modified, the corrosion currents are significantly reduced and the corrosion potentials are increased. Figure 3 These are the test and evaluation results of the acid resistance of the powders of Examples 1, 2 and 3 before and after coating, indicating that the acid resistance of the three powders is improved after coating. Figure 4 It is a simple schematic diagram of the preparation method of the present invention.

[0062] It can be seen from the above embodiments that the present invention adopts an in-situ polymerization method, firstly coating a layer of modifier and preservative on the carbonyl iron powder, and then coating a layer of resin through a cross-linking curing reaction, and finally forming a double-shell structure of resin @ preservative @ carbonyl iron powder. The materials used are all organic materials, all of which are low-dielectric materials, which can reduce the dielectric properties of carbonyl iron powder, optimize impedance matching, and improve reflection loss. Finally, the present invention significantly improves the acid resistance, electrochemical corrosion resistance, and salt spray resistance of the modified powder without much deterioration in the electromagnetic properties of the powder, and can achieve coating for carbonyl iron powders of various shapes, providing a new solution for improving the corrosion resistance of carbonyl iron powder.

Claims

1. A method for preparing microcapsule composite carbonyl iron powder coated with organic material, characterized in that: The following steps are involved: Step 1, at room temperature, dissolving a preservative and a modifier in an organic solvent to obtain a mixture A; in the mixture A, by mass fraction, the preservative accounts for 12% to 24%, the modifier accounts for 12% to 24%, and the organic solvent accounts for 52% to 76%, and the sum of the three is 1; The preservative is one or more of 2-amino-4-methylpyridine, N,N'-di(diphenylphosphino)-1-phenylethylamine, and n-hexadecylamine; The modifier is one or two of diethylaminopropylamine, triethylenetetramine and hexamethylenediamine; Step 2, adding carbonyl iron powder to the mixture A obtained in step 1, and dispersing evenly to obtain a mixture B; in the mixture B, the carbonyl iron powder accounts for 30% to 50% by mass, the mixture A accounts for 50% to 70% by mass, and the sum of the two accounts for 1; Step 3, filtering the mixture B obtained in step 2, washing with deionized water in sequence, and vacuum drying to obtain a carbonyl iron powder coated with a layer of modifier and preservative; Step 4, dissolving the resin in an organic solvent to obtain a mixture C; in the mixture C, the resin accounts for 2% to 8% by mass, the organic solvent accounts for 92% to 98% by mass, and the sum of the two accounts for 1; Step 5, adding a crosslinking aid, an emulsifier and the carbonyl iron powder obtained in step 3 to the mixture C obtained in step 4, and then heating and stirring the mixture until the crosslinking reaction is complete to obtain a mixture D; In mixture D, by mass fraction, the crosslinking agent accounts for 1% to 4%, the emulsifier accounts for 1% to 4%, the carbonyl iron powder accounts for 7% to 14%, and the mixture C accounts for 78% to 91%, and the sum of the four accounts is 1; The cross-linking aid is one or two of phthalic anhydride, tetrahydrophthalic anhydride, and N,N-dimethylpiperazine; the emulsifier is one or two of sorbitan monooleate, sorbitan monooleate, and sodium lauryl sulfate; Step 6: Cool the mixture D obtained in step 5 to room temperature, and then perform suction filtration, deionized water washing and vacuum drying in sequence to finally obtain microcapsule composite carbonyl iron powder coated with organic material.

2. The method for preparing the organic material-coated microcapsule composite carbonyl iron powder according to claim 1, characterized in that: The organic solvent is acetone, xylene, n-butanol or ethanol.

3. The method for preparing the organic material-coated microcapsule composite carbonyl iron powder according to claim 1, characterized in that: The carbonyl iron powder is spherical, so that the finally obtained microcapsule composite carbonyl iron powder coated with organic material has better corrosion resistance.

4. The method for preparing the organic material-coated microcapsule composite carbonyl iron powder according to claim 1, characterized in that: The carbonyl iron powder is in the form of flakes, so that the finally obtained microcapsule composite carbonyl iron powder coated with organic material has better electromagnetic properties.

5. A microcapsule composite carbonyl iron powder coated with an organic material, characterized in that: Prepared by the method of claim 1.

Citation Information

Patent Citations

  • Anti-corrosion treatment method for iron powder

    CN112563010A

  • Rust-resistant carbonyl iron powder wave-absorbing material and preparation method thereof

    CN113388231A

  • Composite electromagnetic medium material containing dicyclopentadienyl iron phthalocyanine metal organic magnetic body and preparation method thereof

    CN101692366A

  • Manufacturing method of Mo2FeB2 based steel bonded hard alloy

    CN102618769A